Equestrian drama
1 online resource
Keywords: "Equestrian Drama: An Anthology of Plays is a collection of four representative plays from the equestrian drama genre of dramatic literature. The book includes annotated play scripts for Timour the Tartar by Matthew Lewis, The Battle of Waterloo by J.H. Amherst, Mazeppa by Henry M. Milner, and The Whip by Henry Hamilton and Cecil Raleigh. An introduction precedes the collection, providing the necessary information to understand and contextualize the genre and the plays within the time period of their original productions, as well as within the larger histories of theatre and equestrian entertainments. Additional related plays are identified, excerpted, and explored, providing readers with a wide range of examples to better understand the development and significance of this unique form of dramatic literature. The book also highlights the contributions made to stage technology and design by the patented stage machinery designed for the production of the mechanized form of equestrian drama, which became popular in the late nineteenth century. Equestrian Drama is suitable for undergraduate, graduate, and professional students in dramatic literature, theatre history, performance studies, and equine studies. An online supplement to this book is available to provide readers with additional content relating to this collection, including original English language translations of La Fille Hussard and Rognolet and Passe-Carreau, as well as the full annotated text of Turpin's Ride to York"--